Existing knowledge on Zn status biomarkers (1963–2021) with a particular focus on FADS1 and FADS2 diagnostic performance and recommendations for further research - Knez, Marija; Boy, Erick (Frontiers Media, 2023)
The role of Zn in human health was discovered 60 years ago, and despite remarkable research efforts, a sufficiently sensitive and specific biomarker of Zn status is still lacking. Plasma/serum Zn, currently the best available and most accepted population Zn status indicator, responds well to severe Zn deficiency, yet, mild to moderate Zn deficiency states usually remain unrecognized. Identifying early-stage Zn deficiency requires additional robust markers of Zn status. This paper discusses the sensitivity, specificity, and responsiveness of plasma Zn concentrations to Zn interventions. It describes the biochemical and dietary basis for the causal association between Zn and fatty acid desaturases activity, FADS1 and FADS2, based on data collected through studies performed in animals and/or humans. The influence of potential confounders and covariates on the observed relationships is considered. Additional potential Zn biomarkers are discussed and suggestions for further research in this area are provided.